Prevalence and Associated Factors of Erectile Dysfunction among Married Men in Vietnam - Van Vo, Thang; Hoang, Hue Dinh; Thanh Nguyen, Nhan Phuc (Frontiers in Public Health, 2017)
Background: Sexuality is an essential part of life; however, erectile dysfunction (ED) has been one of the most common complaints among men with sexual health issues all over the world. ED includes dysfunction in erection and penile erectile pain. Aims: To identify the prevalence of ED and its associated variables and the need among married men for treatment of ED. Methods: This was a cross-sectional study. A total sample size included 746 married men, aged 20-60 years, living in 4 representative wards of the Hue City and randomly selected by systematic sampling method. Respondents completed a self-reported questionnaire. The International Index of Erectile Function (IIEF-5) scale was to determine ED severity and Depression Anxiety Stress Scales (DASS-21) was to measure depression, anxiety and stress. Quality of life was assessed using the WHO Quality of Life score (WHOQoL). A multivariate logistic regression model was used to determine the relationships between independent variables and ED. Results: Mean age of married men was 44.3 ± 8.7. 66.9% of respondents experienced ED symptoms. In terms of severity, 40.8% reported mild ED; 20.3% mild-moderate ED; 5.0% moderate ED and 0.8% severe ED. Depression, anxiety and stress problems were 5.0%, 3.6% and 2.8%, respectively. 33.1% of the respondents reported having low quality of life, and 32.6% reported having medium quality of life. The vast majority (86.9%) had consensual sex with their wives/partners. Variables associated with increased IIEF-5 score were increasing WHOQoL score, increased BMI, religion, no consumption of alcohol. Increasing age, disease history, increased anxiety and no consensual sex with their wife/partner were negatively associated with ED. If experiencing ED, 55.5% would seek help from medical doctors, 55.1% discussed it with their wives/partners and 23.1% turned to their friends for help. Conclusions: The prevalence of ED was high, although only 5.8% experienced moderate to severe ED. The key factors affecting ED were founded as age, religion, disease history, BMI, alcohol consumption, anxiety, quality of life and consensual sex with their wives/partners. Sexual health education should be more specifically targeted for men, including the provision of local sexual health care services for men at need.